Los hábitos de estudios y su incidencia en el rendimiento académico de los estudiantes del octavo año de educación básica, sección vespertina del colegio nacional en ciencias Juan Montalvo de la ciudad de Machala 2012 - 2013. - Ramírez Cabrera, Giovanni Mauricio (2014)
This research content was developed in the province of El Oro , a city of Machala , at the National College of Science Juan Montalvo , with a universe of 100 students of the eighth year of basic education .